Corporate leadership and its role in shaping organizational culture and performance - Bejaoui, Azza (IGI Global, 2019)
"This book explores the effect of CEO/Director behavior on firm performance across the world. It also focuses on corporate finance, strategic management, corporate governance, and behavioral finance"--